Enhancement of Anti-Tumoral Properties of Paclitaxel Nano-Crystals by Conjugation of Folic Acid to Pluronic F127: Formulation Optimization, In Vitro and In Vivo Study - Nagaraja Sreeharsha; Samathoti Prasanthi; Satyavarapu Veera Venkata Naga Satya Mahalakshmi; Prakash S. Goudanavar; Nimbagal Raghavendra Naveen; Buduru Gowthami; Santosh Fattepur; Girish Meravanige; Syed Mohammed Basheeruddin Asdaq; Md. Khalid Anwer; Bandar Aldhubiab; Mohammed Monirul Islam; et al. (Molecules, 2022)
A brand-new nano-crystal (NC) version of the hydrophobic drug Paclitaxel (PT) were formulated for cancer treatment. A stable NC formulation for the administration of PT was created using the triblock co-polymer Pluronic F127. To achieve maximum entrapment effectiveness and minimal particle size, the formulation was improved using the central composite design by considering agitation speed and vacuum pressure at five levels (coded as +1.414, +1, 0, −1, and −1.414). According to the Design Expert software’s predictions, 13 runs were created and evaluated for the chosen responses. The formulation prepared with an agitation speed of 1260 RPM and a vacuum pressure of 77.53 mbar can meet the requirements of the ideal formulation in order to achieve 142.56 nm of PS and 75.18% EE, according to the level of desirability (D = 0.959). Folic acid was conjugated to Pluronic F127 to create folate receptor-targeted NC. The drug release profile of the nano-crystals in vitro demonstrated sustained release over an extended period. Folate receptor (FR)-targeted NC (O-PT-NC-Folate) has also been prepared by conjugating folic acid to Pluronic F127. MTT test is used to validate the targeting efficacy on the FR-positive human oral cancer cell line (KB). At pharmacologically relevant concentrations, the PT nano-crystal formulation did not cause hemolysis. Compared to non-targeted NC of PT, the O-PT-NC-Folate showed a comparable but more sustained anti-cancer effect, according to an in vivo anti-tumor investigation in NCI/ADR-RES cell lines. The remarkable anti-tumor effectiveness, minimal toxicity, and simplicity of scale-up manufacturing of the NC formulations indicate their potential for clinical development. Other hydrophobic medications that are formulated into nano-systems for improved therapy may benefit from the formulation approach.